Antioxidant status and odour profile in milk from silage or lucerne-fed cows - Rossetti, Luciana; Langman, Leandro Ezequiel; Grigioni, Gabriela Maria; Biolatto, Andrea; Sancho, Ana Maria; Comeron, Eduardo Alberto; Descalzo, Adriana Maria (Dairy Industry Association of Australia, 2022)
In order to determine the effect feeding differences on natural antioxidant vitamin delivery, two contrasting diets, lucerne (ALF) and sorghum silage (SS), were analysed. Diets showed different profiles for fat-soluble vitamins. ALF was higher in α-tocopherol, β-carotene and retinol than the SS diet. On the contrary, SS diet was higher in γ- and δ- tocopherol, due to the soy expeller contribution in these isomers. The ALF diet favoured higher milk production and protein yield in comparison to SS, whereas the fat content was the opposite (p<0.01). The composition of the diets was partially reflected in milk. The ALF diet favoured the incorporation of α-tocopherol, retinol, β-carotene and vitamin D3 into raw milk. Meanwhile, a less abundant isomer of vitamin E, γ-tocopherol, was significantly higher in the SS than the ALF milk and δ-tocopherol was not detected. In addition, the ALF diet also promoted higher antioxidant activity. The ferric reduction antioxidant power (FRAP) was significantly higher in ALF than in SS milk, however oxidation determined by thiobarbituric acid reactive substances (TBARS) was similar for both types of milk. Also, no differences in ascorbic acid concentration were detected in either type of milk. The ALF and SS milks were clearly separated (100%) by their antioxidant status and odour profiles as a function of feeding into SS and ALF groups when the biochemical variables and sensor LY2/gCTI were analysed together. Two linear Fischer’s discriminant functions were defined according to dietary treatments using β-carotene and sensor LY2/gCTI. The success rate of correct classification of each sample was 100%, either for the original cases or after crossvalidation (p<0.0001). The use of an electronic nose proved to be a useful instrumental method to discriminate the odour profile of milk samples with a different antioxidant status. // Resumen: Con el fin de determinar el efecto de las diferencias de alimentación sobre el suministro de vitaminas antioxidantes naturales, se analizaron dos dietas contrastantes, alfalfa (ALF) y ensilaje de sorgo (SS). Las dietas mostraron diferentes perfiles de vitaminas liposolubles. ALF fue más alto en α-tocoferol, β-caroteno y retinol que la dieta SS. Por el contrario, la dieta SS fue más alta en γ- y δ- tocoferoles, debido al aporte del expulsor de soya en estos isómeros. La dieta ALF favoreció una mayor producción de leche y proteína en comparación con SS, mientras que el contenido de grasa fue todo lo contrario (p<0,01). La composición de las dietas se reflejó parcialmente en la leche. La dieta ALF favoreció la incorporación de α-tocoferol, retinol, β-caroteno y vitamina D3 a la leche cruda. Mientras tanto, un isómero menos abundante de vitamina E, γ-tocoferol, fue significativamente mayor en la leche SS que en la ALF y no se detectó δ-tocoferol. Además, la dieta ALF también promovió una mayor actividad antioxidante. El poder antioxidante de reducción férrica (FRAP) fue significativamente mayor en ALF que en SS, sin embargo, la oxidación determinada por sustancias reactivas al ácido tiobarbitúrico (TBARS) fue similar para ambos tipos de leche. Además, no se detectaron diferencias en la concentración de ácido ascórbico en ninguno de los dos tipos de leche. Las leches ALF y SS estaban claramente separadas (100 %) por su estado antioxidante y perfiles de olor en función de la alimentación en los grupos SS y ALF cuando las variables bioquímicas y el sensor LY2/gCTI fueron analizados juntos. Se definieron dos funciones discriminantes lineales de Fischer según los tratamientos dietéticos utilizando β-caroteno y el sensor LY2/gCTI. La tasa de éxito de la clasificación correcta de cada la muestra fue del 100%, ya sea para los casos originales o después de la validación cruzada (p<0,0001). El uso de una nariz electrónica demostró ser un método instrumental útil para discriminar el perfil de olor de muestras de leche con un estado antioxidante diferente.